1988
DOI: 10.1590/s0004-282x1988000300002
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary essential tremor in Buenos Aires (Argentina)

Abstract: A descriptive trial of essential tremor in Buenos Aires city is proposed. It may be considered as the first one like this in Latin America. During a 15 year period, sixteen families with essential tremor diagnosis have been examined, making a total of 39 patients (20 males and 19 females). The disease was basically studied from its semiological, clinico-evolutive and therapeutical view point, following a protocol. Our results indicate -- a. The clinico-evolutive characteristics: its frequency (according to rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Headhoice tremor occurs more often and is more severe in women. It has previously been reported that headhoice tremor occurs in -30% of ET patients (4,5,8,(11)(12)(13). This estimate closely agrees with our observations among male patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Headhoice tremor occurs more often and is more severe in women. It has previously been reported that headhoice tremor occurs in -30% of ET patients (4,5,8,(11)(12)(13). This estimate closely agrees with our observations among male patients.…”
Section: Discussionmentioning
confidence: 98%
“…ET appears most frequently in the hands: -90% of ET patients have hand tremor (4,5,8,(11)(12)(13). The next most frequently affected body area is the cranial musculature, with headhoice tremor affecting -30% of patients; other body regions are much more rarely affected.…”
mentioning
confidence: 99%